An open-label prospective observational study to evaluate the efficacy and safety of alternate day versus daily dosing of atorvastatin in patients of dyslipidemia - Gulam Mohammad; Shivangna Singh; Priti Singh; Gautam, Vivek; Vijai Ananth Pitchai Pillai (Asian Journal of Medical Sciences, 2024)
Background: Hypercholesterolemia is a main driver of atherosclerosis. Cholesterol-containing lipoproteins induce endothelial dysfunction and macrophage activation. Foam cell formation results from the uptake of cholesterol-containing lipoproteins by macrophages, it is an essential step in the initiation and progression of atherosclerosis. Aims and Objectives: To evaluate the efficacy and safety of alternate day versus daily dosing of atorvastatin in patients with dyslipidemia. Materials and Methods: This open-label, prospective, observational study was conducted on dyslipidemic patients who came into the medicine Outpatient Department of Dhanalakshmi Srinivasan Medical College and Hospital, Tamil Nadu. Approval for the study was taken from the Institutional Ethical Committee. The duration of the study was 3 months. The efficacy of atorvastatin was checked by noting their blood lipid profile status. Results: Out of 100 patients included in the study 79 completed the study whereas 21 patients were lost in follow-up, 42 patients were analyzed in daily dose (Group A), and 37 patients in alternate dose (Group B) of atorvastatin (20 mg). There was no statistically significant difference based on triglyceride, total cholesterol, low-density lipoprotein, and high-density lipoprotein levels both prior and post-treatment in both the groups. Adverse drug reactions (ADR) profile showed a statistically significant difference between both the groups after treatment by atorvastatin (P=0.0001), with more ADRs noted in a daily dosing group. Conclusion: The results of this study show that alternate dosing of atorvastatin was better tolerated than daily dosing hence physicians can consider choosing an alternate day therapy to reduce pill burden on patients.